Serum concentrations of vitamin E and carotenoids are altered in Alzheimer's disease: A case‐control study. Issue 3 (19th July 2017) - Mullan, Kathryn; Williams, Michael A.; Cardwell, Chris R.; McGuinness, Bernadette; Passmore, Peter; Silvestri, Giuliana; Woodside, Jayne V.; McKay, Gareth J.
Abstract: Introduction: Oxidative stress has been implicated in the pathogenesis of Alzheimer's disease (AD). We investigated associations between serum levels of lipophilic antioxidants and AD. Methods: Serum concentrations of retinol, two forms of vitamin E (α‐ and γ‐tocopherol) and six carotenoids were quantified by high‐performance liquid chromatography from patients with AD ( n  = 251) and cognitively intact controls ( n  = 308) and assessed by regression analyses. Results: Serum levels of α‐tocopherol and all six carotenoids were significantly lower in patients with AD compared with cognitively intact controls ( P  < .001). In contrast, γ‐tocopherol was significantly higher in the serum of patients with AD (odds ratio = 1.17 [confidence intervals: 1.05–1.31]). Discussion: Our findings implicate compromised serum antioxidant defenses in AD pathogenesis and differing biological roles for vitamin E isoforms. This highlights the need for improved understanding in the balanced upregulation of exogenous antioxidants related to dietary intake or supplement use in future nutritional intervention studies.